Parental attachment as the predictor of emerging adulthood experiences - Walton Wider; Mazni Mustapha; Ferlis Bahari; Murnizam Halik (2016)
This study examines the predictor of parental attachment towards emerging adulthood (EA) experiences among 548 undergraduate students (202 males, 346 females, and mean age of 20.8 years) aged between 18 and 25 in East Malaysia. The Inventory of Parent and Peer Attachment (IPPA) was used to measure the components of parental attachment (Trust, Communication, and Alienation), and the Inventory of Dimensions of Emerging Adulthood (IDEA) was used to measure five experiences of EA (identity exploration, self-focus, feeling “in-between”, possibilities, and instability). This study used variance-based structural equation modelling via partial least squares (PLS) to test the hypotheses. The results revealed that parental trust is the most significant predictor of EA experiences of identity exploration, self-focus and possibilities, whereas parental communication is the most significant predictor of EA experience feeling “in-between”, and parental alienation is the most significant predictor of EA experience of instability.